Puesta a punto de las condiciones para la medición de corrientes de calcio evocadas del receptor NMDA y evaluación de la viabilidad celular de un cultivo primario de neuronas de hipocampo en presencia del péptido sintético Pb53a. (2022)
The activity of the N-methyl-D-aspartate glutamate receptor (NMDAR) is closely related to synaptic plasticity and learning and memory processes. Overactivation of NMDAR triggers the entry and sustained increase of calcium ion concentration at neuronal level, causing, among others, increased excitability, altered metabolism, neuronal damage and neuronal death, as observed in pathologies such as schizophrenia, Alzheimer's disease, Parkinson's disease, epilepsy and cerebral ischemia. In this work we proposed to set up the conditions to evaluate the effect of the synthetic peptide Pb53a derived from the spider toxin Phoneutria boliviensis on NMDA receptor activity in hippocampal neurons using the patch clamp technique